Transitions to entrepreneurship and industry-specific barriers - Magnus Lofstrom; Timothy Bates; Simon C. Parker (Institute for the Study of Labor (IZA), 2011)
Drivers of entrepreneurial entry are investigated in this study by examining how entry into small-business ownership is shaped by industry-specific constraints. The human- and financial-capital endowments of potential entrepreneurs entering firms in various industries are shown to differ profoundly, depending on the type of venture entered. The educational credentials of highly educated potential entrepreneurs, in particular, predict avoidance of small-firm ownership in some industries as well as attraction to others. Recognizing that individuals choose an industry sector jointly with their decision to enter entrepreneurship, we find that the conventional practice of conflating different industry types in empirical analyses of transitions to entrepreneurship generates misleading findings about the determinants of entrepreneurship.
urn:nbn:de:101:1-201111213417
Keywords: J24; L26; M13; 330; entrepreneurship; self-employment; capital constraints; transitions; entry barriers; business start-ups; Unternehmer; Unternehmensgründung; Markteintritt; Branche; Verschuldungsrestriktion; Selbstständige; Schätzung; USA